2003
DOI: 10.1101/gad.1101303
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ is essential for Dishevelled function in a noncanonical Wnt pathway that regulatesXenopusconvergent extension movements

Abstract: Protein kinase C (PKC) has been implicated in the Wnt signaling pathway; however, its molecular role is poorly understood. We identified novel genes encoding ␦-type PKC in the Xenopus EST databases. Loss of PKC␦ function revealed that it was essential for convergent extension during gastrulation. We then examined the relationship between PKC␦ and the Wnt pathway. PKC␦ was translocated to the plasma membrane in response to Frizzled signaling. In addition, loss of PKC␦ function inhibited the translocation of Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 65 publications
7
139
0
Order By: Relevance
“…Among the diverse signal transduction pathways mediated by Dvls, regulation of small GTPase activity and following rearrangement of actin cytoskeleton is one of the most important cellular processes, including development, neurite retraction (Kishida et al, 2004), cell motility, migration (Endo et al, 2005), etc. As it has been reported that several kinases for the phosphorylation of the Dvl family are involved in response to ligand stimulation (Hino et al, 2003;Kinoshita et al, 2003; , we screened a possible candidate kinase(s) by treating a variety of kinase inhibitors, and found that the treatment of CK1-specific inhibitor, D4476, effectively suppressed the phosphorylation of Dvl2 and Dvl3. Involvement of CK1 in the Wnt-related signaling pathway has been implicated recently; CK1 enhances Wnt-3a-induced activation of the b-catenin signaling through Dvl-1 and Frat-1 binding (Hino et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the diverse signal transduction pathways mediated by Dvls, regulation of small GTPase activity and following rearrangement of actin cytoskeleton is one of the most important cellular processes, including development, neurite retraction (Kishida et al, 2004), cell motility, migration (Endo et al, 2005), etc. As it has been reported that several kinases for the phosphorylation of the Dvl family are involved in response to ligand stimulation (Hino et al, 2003;Kinoshita et al, 2003; , we screened a possible candidate kinase(s) by treating a variety of kinase inhibitors, and found that the treatment of CK1-specific inhibitor, D4476, effectively suppressed the phosphorylation of Dvl2 and Dvl3. Involvement of CK1 in the Wnt-related signaling pathway has been implicated recently; CK1 enhances Wnt-3a-induced activation of the b-catenin signaling through Dvl-1 and Frat-1 binding (Hino et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of the Dvl family protein has been reported and a large number of kinases were implicated to be involved (Hino et al, 2003;Kinoshita et al, 2003;Wharton, 2003;Bryja et al, 2007a). To examine a kinase possibly involved in the FZD10-induced phosphorylation of Dvl2 and Dvl3, FZD10-positive cell lines were treated with various kinase inhibitors and effects on their phosphorylation levels were investigated.…”
Section: Regulation Of Dvl2 and Dvl3 By Fzd10mentioning
confidence: 99%
“…Many of FZD receptors, including FZD3 and FZD7, are able to activate the canonical b-catenin pathway, whereas data are not so obvious for FZD6. The noncanonical PKC and JNK pathways have been clearly shown as potentially activated by some FZD family members as FZD7, whereas it remains ambiguous for FZD3 and FZD6 (He et al, 1998;Winklbauer et al, 2001;Kinoshita et al, 2003;Merle et al, 2004;Katoh, 2007;Katoh and Katoh, 2007b). We have previously reported that the FZD7-mediated signalling was able to control the cancerous phenotype of human HCC cell lines through b-catenin protein regulation, and that one of the Wnt ligand candidate activators is WNT3 (Merle et al, 2004(Merle et al, , 2005Kim et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that Dsh (PDZ domain) and JNK activity are required for gut elongation, whereas ROCK and PKC activity are required for midline convergence of the foregut organs, with Dsh (DEP domain) and Rac activity being essential for both convergence and extension. This is reminiscent of CE in the gastrula mesoderm where Wnt11 signals via Dsh (both the PDZ and DEP domains), Rac, JNK, Rho, ROCK, and PKC to coordinate dynamic cell behaviors, with each of the components having both distinct and overlapping functions (Yamanaka et al 2002;Habas et al 2003;Kinoshita et al 2003;Tahinci and Symes 2003;Kim and Han 2005).…”
Section: Noncanonical Wnt/pcp Signaling Regulates Gut Morphogenesismentioning
confidence: 99%